Synchronous Multiplayer Shooting in the 2D Game "War Cops" Using Unity Engine - Geubrina, Tiara; Husaini, Husaini; Mahlil, Mahlil (Journal of Artificial Intelligence and Software Engineering, 2024)
In this modern era, the digital game industry continues to grow rapidly with various innovations in game creation. One of the game development platforms that is often used is the Unity Engine. Currently, developed games are only played offline, and users must buy special devices. To overcome this problem, innovation is needed to allow players to play together without these restrictions. In this effort, Unity Engine 2D can be used with Photon Unity Network support for games over different networks. This study aims to determine the response speed of Photon. The results show that the ping test response from the photon obtained an average value of 201 ms.